On contemporary computational mechanics - Mang, Herbert (Journal of Civil Engineering and Management, 2009)
It is a great pleasure to inform the readers that Prof. Herbert A. Mang, an active member of Editorial Board, on April 30, 2007, was given a prestigious award, the Carl-Friedrich-Gauß-Medal, by the Braunschweigische Wissenschaftliche Gesellschaft (BWG). Congratulations! This medal has been awarded annually once since 1949. Among the awardees are several laureates of the Nobel Prize.The laudation was held by Prof. Peter Wriggers, President of the Gesellschaft fuer Angewandte Mathematik und Mechanik (GAMM). On this occasion Prof. Mang gave a lecture. We expect that printing of a translation of this lecture, reflecting the achievements in Computational mechanics of a research group led by Prof. Herbert A. Mang (http://www.imws.tuwien. ac.at/en/team/management/herbert-mang.html), a prominent and world-renowned scientist, would be interesting for the readers.First Published Online: 14 Oct 2010